Evaluation Of Three Energy EfficientOffice Buildings On Architectural AndPassive Design Strategy Towards Cost Effectiveness - Naamandadin, Nurul Akmam (2011)

(untitled)
The lack of systems to disseminate information on the knowledge and technological characteristics of energy conservations, energy productions and energy usage in the construction industry has led to a publication of Malaysia Standard: Code of Practice on Energy Efficiency and Use of Renewable Energy for Non-Residential Buildings (MS 1525:2007). This study was carried out with reference to the architectural and passive design strategy stated in MS 1525:2007. The assessments to the site planning and orientation, facade design, ventilation, strategic landscaping and future consideration of renewable energy were made on three selected energy efficient office buildings which are Securities Commission Building,Mesiniaga Tower and LEO Building.